Implementasi Kebijakan Asuransi Usaha Tani Padi (AUTP) Di Desa Upang Ceria Kecamatan Muara Telang Kabupaten Banyuasin - Yuliansyah, Andrian; Saswita, Saswita; Hestirinaih, Deby Chintia (@-Publik: Jurnal Administrasi Publik, 2024)
This research is titled “Implementation of the Rice Farming Business Insurance Policy (AUTP) in Upang Ceria Village, Muara Telang Sub-district, Banyuasin Regency.”The objectives of this study are:1)To identify and analyze the implementation of the Rice Farming Business Insurance Policy (AUTP) in Upang Ceria Village, Muara Telang Sub-district, Banyuasin Regency. 2)To identify and analyze the supporting and inhibiting factors in the implementation of the Rice Farming Business Insurance Policy (AUTP) in Upang Ceria Village, Muara Telang Sub-district, Banyuasin Regency. The research method employed is a qualitative approach with a case study design. The data used consists of primary and secondary data. The data collection instruments include observation, interviews, and documentation. Interviews were conducted with officials from the Banyuasin Regency Office of Food Crops and Horticulture responsible for the implementation of the AUTP program, Field Agricultural Extension Officers (PPL) from Upang Ceria Village, and several farmers. The results of the study show that significant supporting factors contributing to achieving the program's goals include the premium payment facilitation program for rice farming businesses, executive and legislative support for agricultural insurance development, and the use of information technology (SIAP). However, several inhibiting factors were identified, such as the low participation rate of farmers in the AUTP program, the considerable distance of Jasindo's location from Banyuasin Regency, limited operational budgets at the regency level, suboptimal communication by policy implementers, and the insufficient number of personnel handling this sector.